Living With Brain Cancer In David Nixon's Letters To God Movie (2010): An Individual Psychological Approach - Sasmita, Aniendia Indah Permatawati (2012)
The major problem in this research paper is to explain how living with brain cancer is reflected in Letters to God movie. The purpose of this research paper is to analyze Tyler's live in David Nixon's Letters to God movie based on the structural element of the movie and based on an individual psychological approach. The object study is David Nixon's Letters to God movie. It is using an individual psychological approach. In analyzing this study, the researcher uses qualitative research and individual psychological approach. The primary data source of this research is Letters to God movie. The secondary date sources are material about individual psychology, theory of literature, theory of personality and the other source that support the analysis. Having analyzed this research paper, the researcher present some conclusions. First, based on the structural analysis it is found that in this movie, David Nixon conveys a message that "one must be optimistic even at the worst condition". Second, based on the psychological analysis, it is evident that in this movie David Nixon illustrated a psychological phenomenon in which an individual had a positive attitude in encountering the incurable disease